2021
DOI: 10.1080/24733938.2021.1910333
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying technical actions in professional soccer using foot-mounted inertial measurement units

Abstract: This study aimed to (i) establish the concurrent validity and intra-unit reliability of a foot-mounted inertial measurement unit for monitoring soccer technical actions, (ii) quantify the within-microcycle inter-positional differences in the technical actions of professional soccer training, and (iii) determine the influence of drill category on the technical actions of professional soccer training. Twenty-one professional soccer players' technical performance data (ball touches, releases, ball touches per min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 98 publications
0
31
3
Order By: Relevance
“…Choosing the level at which the classification acceptance threshold is set may require further thought and investigation, or else it may be set at the discretion of practitioners who decide the relative importance of sensitivity and specificity in varying situational circumstance. Furthermore, using additional sensors in alternative locations e.g., the foot [ 22 ], may provide unique data to the trunk-mounted sensor and further improve COD classification.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing the level at which the classification acceptance threshold is set may require further thought and investigation, or else it may be set at the discretion of practitioners who decide the relative importance of sensitivity and specificity in varying situational circumstance. Furthermore, using additional sensors in alternative locations e.g., the foot [ 22 ], may provide unique data to the trunk-mounted sensor and further improve COD classification.…”
Section: Discussionmentioning
confidence: 99%
“…Recording was initiated 10 minutes before activity. As per previous methods [ 49 ], players wore an IMU on each foot, with each device gathering information via a 2000°/sec tri-axial gyroscope and a 16 g tri-axial accelerometer. The gyroscope measured angular velocity of the shank while the accelerometer identified accelerations of the lower leg in the frontal, sagittal and transverse planes of motion.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, IMUs were also able to capture team characteristics including the possession percentage, the number of attempted and successful passes, the mean number of passes per possession, the mean time in possession and the mean time regaining possession. Due to a limitation within the PlayerMaker system when distinguishing between a shot and a pass [ 49 ], all shots at goal were removed from the passing network analysis, with only data that represented when one player released the ball and another received it being included. Using twelve amateur soccer players, who collectively performed 8,640 ball touches and 5,760 releases during a series of technical soccer tasks, repeated over two pre-determined distances, previous research [ 49 ] has shown the concurrent validity (agreement with video analysis) for ball touches and releases to be 95.1% and 97.6% respectively [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations